2022
DOI: 10.3390/healthcare10122531
|View full text |Cite
|
Sign up to set email alerts
|

Information Security Behavior in Health Information Systems: A Review of Research Trends and Antecedent Factors

Abstract: This study aims to review the literature on antecedent factors of information security related to the protection of health information systems (HISs) in the healthcare organization. We classify those factors into organizational and individual aspects. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Academic articles were sourced from five online databases (Scopus, PubMed, IEEE, ScienceDirect, and SAGE) using keywords related to information security, behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…There are numerous opportunities for data theft, so the need for a strong cybersecurity function in healthcare organizations is greater than ever [29]. The implementation of health information systems into the corporate system by healthcare providers has a positive value for managing health information but also has negative impacts, such as security and privacy risks, and therefore needs to be implemented as part of corporate security to ensure all levels of security [31].…”
Section: Current Security Threats In Healthcare Institutions In Sloveniamentioning
confidence: 99%
“…There are numerous opportunities for data theft, so the need for a strong cybersecurity function in healthcare organizations is greater than ever [29]. The implementation of health information systems into the corporate system by healthcare providers has a positive value for managing health information but also has negative impacts, such as security and privacy risks, and therefore needs to be implemented as part of corporate security to ensure all levels of security [31].…”
Section: Current Security Threats In Healthcare Institutions In Sloveniamentioning
confidence: 99%
“…Another theoretical underpinning, such as Regulatory Focus Theory (RFT), can be used to compare preventive and promotion motivation to influence desirable security behavior. RFT has never been employed in studies of information security behavior in healthcare organizations (Sari et al, 2022). Previous studies utilizing this theory in contexts other than healthcare have found that promotion-focused and prevention-focused approaches can directly influence information security behavior preferences (Shih et al, 2021) or indirectly (Burns, 2021;Hwang & Cha, 2018).…”
Section: Conclusion Contribution and Future Workmentioning
confidence: 99%
“…Other researchers have looked at a variety of factors that influence compliance behavior with organizational security policies (Foth et al, 2012;Pathania & Rasool, 2019;Sher et al, 2017), information security regulations (Brady, 2011;Foth, 2016;Johnston & Warkentin, 2008), and information security standards (Alexandrou & Chen, 2019;Fernández-Alemán et al, 2015). According to the outcomes of a systematic literature review (Sari et al, 2022), previous studies in information security behavior in the healthcare context typically employ theoretical foundations such as Protection Motivation Theory (PMT) and General Deterrence Theory (GDT) in conjunction with other theories such as Theory of Planned Behavior (TPB), Theory of Acceptance Model (TAM), Social Cognitive Theory (SCT), Rational Choice Theory (RCT), and many others. However, these theories have been used to investigate healthcare staff 's security behavior in developed countries.…”
Section: Introductionmentioning
confidence: 99%